English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-03 09:57:54 · 20 answers · asked by pvamu19 1 in Science & Mathematics Mathematics

20 answers

8y-6=5y+12
8y-5y=12+6
3y=18
y=18/3
y=6

2006-12-04 16:11:49 · answer #1 · answered by arpita 5 · 0 0

Y=6

2006-12-03 09:59:49 · answer #2 · answered by That guy 2 · 0 0

6

2006-12-03 16:44:38 · answer #3 · answered by Mehbooba 4 · 0 0

It's a simply problem take a look....
8y-6=5y+12 first get the y on the 1 side and the number or consistent on the other.
8y-6=5y+12
+6 +6
8y=5y+18
-5y 5y
3y = 18
divide 3
y = 6

2006-12-03 10:07:42 · answer #4 · answered by Best Helper 4 · 0 0

6

2006-12-03 10:00:35 · answer #5 · answered by chattinforgod 2 · 0 0

6

2006-12-03 09:59:11 · answer #6 · answered by Tim N 5 · 0 0

Hon, you're posting a lot of Algebra questions. You must be stuck on homework, lol.

Anyway, let's take this step by step, hopefully you'll get it with my weak explanations.

Problem: 8y - 6 = 5y + 12

Now you need to cancel one of the number with the y variable. I'll do this because it's easier:

8y - 6 = 5y +12
-5y -5y

8 - 5 = 3 ; 5 - 5= 0

Now that you canceled the 5y with its opposite, you now got:


3y - 6 = 12

We need to set it in the "y = #" form. SO we need to cancel the constant with the 3y by doing the opposite.

3y - 6 = 12
+ 6 =+6


Remember, you can do almost anything to an equation, but you have to do the same on other.

3y = 18 because we canceled the 6.

Now we need to get it down to y = #. How? We divide whatever is with the y.

3y = 18

3/3 = y 18/3 = 6

So y = 6

2006-12-03 10:09:40 · answer #7 · answered by Zuu_zuu 3 · 0 0

Y is 6

2006-12-03 10:02:30 · answer #8 · answered by Male_42_us 2 · 0 0

8y-6=5y+12 subtract 5y from each side
3y-6=12 add 6 to each side
3y=18 divide by 3
y=6

2006-12-03 10:01:19 · answer #9 · answered by yupchagee 7 · 0 0

8y-6=5y+12
(8-5)y = 12+6
3y = 18
y = 18/3
y = 6

2006-12-03 10:02:35 · answer #10 · answered by geoff b 2 · 0 0

Here's the answer and , more important, the method of solution.



We need to isolate terms with "y" on one side of the equation----------------so , subtract 5y from both sides= 3y - 6 = 12


Now add 6 to both sides = 3y - 6 + 6 = 18

Combine like terms on the left = 3y + 0 = 18, or 3y = 18

18/3 = 6

2006-12-03 10:05:19 · answer #11 · answered by JIMBO 4 · 0 0

fedest.com, questions and answers